Demand-pull creation, public officer’s endorsement, and consumer willingness-to-pay for nutritious iron beans in rural and urban Rwanda - Oparinde, Adewale; Murekezi, Abdoul; Birol, Ekin; Katsvairo, Lister (International Food Policy Research Institute, 2017)
Several studies have suggested demand-pull creation in urban areas as a strategy to drive the adoption of novel agricultural products in rural areas. However, questions remain about whether urban consumers have preferences that are similar to those of rural smallholder producers who produce what they consume. This paper compares urban and rural consumers’ preferences for novel agricultural products by using the case of biofortified iron beans in Rwanda; tests the effects of two marketing levers in field experiments using the Becker-DeGroot-Marshak mechanism; and examines the effect of a public officer’s endorsement on consumer demand for iron beans, along with, and the impact of, information length to inform the design of cost-effective marketing strategies for iron beans. The study results show that with or without information on the nutritional benefits of iron beans, rural and urban consumers have similar preferences for one of the two varieties of iron beans tested, which suggests an avenue for demand-pull creation in the urban area. However, the length of the information and a public officer’s endorsement have no significant effect on consumer demand for iron beans. This paper suggests that providing cogent information on the nutritional benefits could alone be effective in branding and marketing iron beans.